PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP PENJUALAN PADA PT. UNILEVER INDONESIA, TBK. - Yunias Insan Nugroho; Lies Indriyatni (BBM (Buletin Bisnis & Manajemen), 2018)
This study aims to: (1) Know the effect of promotion costs on sales at PT. Unilever Indonesia, Tbk. (2) Knowing the influence of distribution cost to sales at PT. Unilever Indonesia, Tbk. (3) Knowing the influence of promotion cost and distribution cost simultaneously to sales at PT. Unilever Indonesia, Tbk. The object of this research is PT. Unilever Indonesia, Tbk. Data taken over 8 years from 2008 - 2015 and calculations using quarterly data consisting of promotional costs, distribution and sales costs. Data collected by documentation method obtained through official website of PT. Unilever Indonesia, Tbk. The data analysis tool used is multiple linear regression analysis and significance test using t test and F test. The results showed that: (1) There is no influence of promotion cost to sales with t arithmetic = 1.778 smaller than t table = 2.0452 with 5% significance; (2) there is positive influence and significant distribution cost to sales with t arithmetic = 17,193 bigger than t table = 2.0452 with significance 5%; (3) There is significant influence of promotion cost and distribution cost simultaneously to sales with F arithmetic = 2057,00 bigger than F table = 3,33 with error level 5%. Keywords: Promotion Cost, Distribution Cost and Sales